Stable morphology, but dynamic internal reorganisation, of interphase human chromosomes in living cells. - Iris Müller; Shelagh Boyle; Robert H Singer; Wendy A Bickmore; Jonathan R Chubb (PLoS ONE)
Despite the distinctive structure of mitotic chromosomes, it has not been possible to visualise individual chromosomes in living interphase cells, where chromosomes spend over 90% of their time. Studies of interphase chromosome structure and dynamics use fluorescence in-situ hybridisation (FISH) on fixed cells, which potentially damages structure and loses dynamic information. We have developed a new methodology, involving photoactivation of labelled histone H3 at mitosis, to visualise individual and specific human chromosomes in living interphase cells. Our data revealed bulk chromosome volume and morphology are established rapidly after mitosis, changing only incrementally after the first hour of G1. This contrasted with the behaviour of specific loci on labelled chromosomes, which showed more progressive reorganisation, and revealed that "looping out" of chromatin from chromosome territories is a dynamic state. We measured considerable heterogeneity in chromosome decondensation, even between sister chromatids, which may reflect local structural impediments to decondensation and could potentially amplify transcriptional noise. Chromosome structure showed tremendous resistance to inhibitors of transcription, histone deacetylation and chromatin remodelling. Together, these data indicate steric constraints determine structure, rather than innate chromosome architecture or function-driven anchoring, with interphase chromatin organisation governed primarily by opposition between needs for decondensation and the space available for this to happen.